2017
DOI: 10.1097/olq.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Gyrase A Genotype of Neisseria gonorrhoeae Predicts In Vitro Susceptibility to Ciprofloxacin: A Systematic Review of the Literature and Meta-Analysis

Abstract: Multidrug-resistant Neisseria gonorrhoeae infections have been declared one of the top three urgent threats to public health. Approaches to combat resistance include targeted therapy with antibiotics previously thought to be ineffective, made possible by rapid molecular assays to predict susceptibility. Previous studies have associated the gyrase A (gyrA) gene of Neisseria gonorrhoeae with in vitro resistance to ciprofloxacin. We conducted a systematic review of studies comparing Neisseria gonorrhoeae gyrA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…In our study, we considered gyrA mutations alone and clearly identified the ciprofloxacin-susceptible and resistant isolates in a single multiplex RT-PCR assay. Thus, our results support the findings by others and demonstrate that the gyrA region alone is sufficient for the determination of ciprofloxacin susceptibility status (13,18,22,26). We determined through DNA sequencing that the majority of isolates with intermediate susceptibility in our study carried mutations only at the S91 or D95 position, and not both ( Table 3); one isolate with intermediate susceptibility in panel 2 had mutations at both S91 and D95 positions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we considered gyrA mutations alone and clearly identified the ciprofloxacin-susceptible and resistant isolates in a single multiplex RT-PCR assay. Thus, our results support the findings by others and demonstrate that the gyrA region alone is sufficient for the determination of ciprofloxacin susceptibility status (13,18,22,26). We determined through DNA sequencing that the majority of isolates with intermediate susceptibility in our study carried mutations only at the S91 or D95 position, and not both ( Table 3); one isolate with intermediate susceptibility in panel 2 had mutations at both S91 and D95 positions.…”
Section: Discussionsupporting
confidence: 90%
“…One study demonstrated detection of N. gonorrhoeae and its ciprofloxacin susceptibility status, but this assay required three consecutive tests for a clear interpretation (27). Several recent publications introduced RT-PCR-based methods for detection of mutations at the gryA S91 locus from clinical specimens (18,26,28). However, these analyses were restricted only to the S91 locus and the assays could be more likely to have errors if ciprofloxacin resistance arose through mutations in the D95 locus.…”
Section: Discussionmentioning
confidence: 99%
“…We characterized the epidemiology of fluoroquinolone resistance at UCLA Health (Los Angeles, CA, USA) by using a rapid molecular gyr A gene assay that predicts ciprofloxacin susceptibility ( 3 , 6 ). UCLA Health is a large healthcare system in Los Angeles County compound of 2 hospitals, 2 emergency departments, and >150 primary care clinics serving ≈500,000 patient-visits each year.…”
Section: The Studymentioning
confidence: 99%
“…To combat this growing threat, we developed and implemented a real-time reverse transcription PCR at the University of California, Los Angeles (Los Angeles, CA, USA), to detect the codon 91 mutation in the gyrase A ( gyr A) gene in N. gonorrhoeae remnant clinical specimens ( 2 ). Mutations in the gyr A gene of N. gonorrhoeae , specifically at codon 91, have been demonstrated to reliably predict resistance to ciprofloxacin ( 3 ).…”
mentioning
confidence: 99%
“…2 The absence of mutation at codon 91 of the gyrase A gene (gyrA) of N. gonorrhoeae has been shown to have both a high sensitivity and specificity (.98%) for predicting N. gonorrhoeae susceptibility to ciprofloxacin. 3 In November 2015, we implemented a laboratory-developed molecular assay for determining the gyrA genotype of all N. gonorrhoeae infections at the University of California, Los Angeles. 4 Our findings showed an increase in the use of ciprofloxacin for the treatment of N. gonorrhoeae infections in clinical practice; however, one limitation of that implementation was the high frequency of indeterminate genotype results, especially among pharyngeal specimens.…”
Section: Introductionmentioning
confidence: 99%